2017
DOI: 10.1002/ccd.27231
|View full text |Cite
|
Sign up to set email alerts
|

Acute and mid‐term outcomes of stent implantation for recurrent coarctation of the aorta between the Norwood operation and fontan completion: A multi‐center Pediatric Interventional Cardiology Early Career Society Investigation

Abstract: SI for treatment of RC in patients after the Norwood operation provides excellent acute relief of obstruction. Intraprocedural hemodynamic instability is common and re-intervention is frequent at mid-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This was studied by Aldoss and colleagues, who reviewed outcomes for stent implantation for recurrent coarctation in the Norwood population in 33 patients at 8 centers. (33) The authors report excellent immediate results of both improvement of the aortic diameter and reduction in the coarctation pressure gradient with stenting. Twelve patients (36%) had SAEs.…”
Section: Catheter Versus Surgical Intervention For Chdmentioning
confidence: 96%
“…This was studied by Aldoss and colleagues, who reviewed outcomes for stent implantation for recurrent coarctation in the Norwood population in 33 patients at 8 centers. (33) The authors report excellent immediate results of both improvement of the aortic diameter and reduction in the coarctation pressure gradient with stenting. Twelve patients (36%) had SAEs.…”
Section: Catheter Versus Surgical Intervention For Chdmentioning
confidence: 96%
“…Transcatheter treatment of aortic arch obstruction in using balloon angioplasty has been well described but may result in inadequate relief of aortic shape with a non-negligible rate of recurrences. Stent implantation has been shown to provide excellent acute relief of aortic arch obstruction but long-term outcomes of this technique in patients with Fontan are necessary to study ( 26 ).…”
Section: Transcatheter Approaches To Fontan Circulation Basic Lesionsmentioning
confidence: 99%
“…In this issue of Catheterization and Cardiovascular Interventions , Aldoss et al have reported the results of a multi‐center retrospective study of 33 patients aged 4.1–13.3 months, weighing 5.2–8.6 kg, who underwent transcatheter stent implantation for recurrent coarctation in single ventricle patients after the Norwood operation but prior to Fontan completion. Twenty‐nine patients (88%) underwent a prior failed balloon angioplasty before stent implantation (SI).…”
mentioning
confidence: 99%